Kondisi Fisik Pemain Sepak Bola Gresik United Football Academy U-16 Tahun 2026 - Hendrie Hindarto; Supriatna (GLOBAL SCIENTS PUBLISHER, 2026)
This study aimed to determine the physical condition of athletes at Gresik United Football Academy U-16 in 2026, covering the components of endurance, speed, agility, and lower-limb muscle power. This research employed a quantitative approach using a descriptive method. The participants consisted of all 23 athletes of Gresik United Football Academy U-16. The research instruments included: (1) the Multistage Fitness Test (MFT) to measure endurance (VO₂max), (2) a 30-meter sprint test to assess speed, (3) an agility test to evaluate agility, and (4) the standing long jump test to measure lower-limb explosive power. Data were analyzed using percentage calculations and Microsoft Excel. The findings revealed that: (1) the average endurance was 49.9 ml/kg/min, categorized as very good; (2) the average speed was 3.83 seconds, categorized as very good; (3) the average agility was 16.82 seconds, categorized as fair; and (4) the average lower-limb explosive power reached 223 cm, categorized as poor. Overall, the test results indicated that the physical condition of Gresik United Football Academy U-16 athletes demonstrated excellent endurance and speed, while agility and explosive power had not yet reached optimal levels. The study concludes that although the players possess strengths in endurance and speed, improvements in agility and explosive power are still necessary through more specific and systematic training programs. Coaches are recommended to design balanced training programs focusing on agility exercises, such as agility drills, ladder drills, and change-of-direction drills. In addition, lower-limb explosive power should be enhanced through structured plyometric training, resistance training, and sprint interval training.